2018
DOI: 10.1097/01.asw.0000546233.35130.a9
|View full text |Cite
|
Sign up to set email alerts
|

Silk-Based Biomaterials in Cutaneous Wound Healing: A Systematic Review

Abstract: OBJECTIVE: Effective wound dressings should promote healing through cellular migration, neovascularization, and re-epithelialization. Silk fibroin (SF) and silk sericin (SS) are reported to have very good biocompatibility, excellent mechanical properties, and controlled biodegradability. This review investigates the use and performance of silk-based biomaterials in cutaneous wounds within in vitro, in vivo, and randomized controlled studies. METHODS: St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…Additionally, SF has been developed into several forms of dressings, including sponges, films, scaffolds, electrospun nanofibers, and hydrogels [ 13 , 14 ]. Silk fibroin exists in alpha-helix and beta-sheet form, both of which are highly biocompatible and can also promote tissue regeneration [ 13 , 15 ]. However, it is difficult for amorphous silk fibroin (α-helix or random coil) to form stable scaffolds [ 16 , 17 ].…”
Section: Introductionsmentioning
confidence: 99%
“…Additionally, SF has been developed into several forms of dressings, including sponges, films, scaffolds, electrospun nanofibers, and hydrogels [ 13 , 14 ]. Silk fibroin exists in alpha-helix and beta-sheet form, both of which are highly biocompatible and can also promote tissue regeneration [ 13 , 15 ]. However, it is difficult for amorphous silk fibroin (α-helix or random coil) to form stable scaffolds [ 16 , 17 ].…”
Section: Introductionsmentioning
confidence: 99%
“…In both in vitro and in vivo studies on wound healing, SF-based biomaterials have demonstrated good cell adhesion and fibroblast proliferation, with improved neovascularization [ 42 ], faster and better tissue healing and complete regeneration in a rat model [ 43 ].…”
Section: Silk Fibroin As a Nature Derived Materials For Wound Healimentioning
confidence: 99%
“…Recent studies have shown that SS is biocompatible and has good biological performance. SS shows great hydrophilic and has multiple biological properties, including anti-oxidation, anti-bacterial, and promoting cell adhesion and proliferation ( 20 , 21 ). However, SS shows poor mechanical properties.…”
Section: Introductionmentioning
confidence: 99%